1996
DOI: 10.1136/adc.75.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol use, availability, and knowledge of toxicity among British and American adolescents.

Abstract: Paracetamol is the commonest agent employed in self poisoning, however it is not clear whether adolescents possess insight into the serious complications associated with its misuse. Using a one page questionnaire, the availability, usage, and knowledge of toxicity of paracetamol among 1147 American and British adolescents was assessed. Although 90% of all sttidents recognised that paracetamol could kill, the great majority of students overestimated the lethal dose. In addition, while knowledge regarding side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…5 6 9 This pattern may well reflect differences in availability, as most adolescents have easy access to paracetamol. 25 In the present study, the age specific distribution among the unselected population from the local region showed the expected distribution, with a predominance of cases in adolescents and young adults. In comparison, transferred patients were significantly older.…”
Section: Discussionsupporting
confidence: 67%
“…5 6 9 This pattern may well reflect differences in availability, as most adolescents have easy access to paracetamol. 25 In the present study, the age specific distribution among the unselected population from the local region showed the expected distribution, with a predominance of cases in adolescents and young adults. In comparison, transferred patients were significantly older.…”
Section: Discussionsupporting
confidence: 67%
“…Only 87 (6%) of 1445 customers could correctly identify at least one side effect for their purchased medicines. This is even less than in other studies (Hughes et al 2002;Gilbertson et al 1996;Cham et al 2002;Mahmud et al 1995), but because of differences in study methods and definitions, results are difficult to compare. We would argue that knowing about benefits and risks of medicines is important for two reasons.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast to this, a range of studies from other developed countries have generally found knowledge about side effects to be poor; in a small sample of the general public in the UK, Hughes et al (2002) reported that only 16% could name at least one side effect of their over-the-counter (OTC) medicines. American and British adolescents' knowledge about side effects of paracetamol was poor (Gilbertson et al 1996). Only 61% of visitors to an emergency department were able to mention at least one side effect of non-steroidal anti-inflammatory drugs (NSAIDs) (Cham et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One study of over 1,000 British and American teens found that teens may markedly overestimate the size of a lethal dose of acetaminophen,(15) while others have found that teens may not comprehend that it is possible to ingest a lethal amount of acetaminophen. (1618) Motivated by the potential risks of acetaminophen and evidence that adolescents may commonly self-administer pain medicines without parental oversight, we examined understanding of acetaminophen among a sample of adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%